Analysis of the Level of Understanding of the Binjai City Public Towards the Use of Non-Cash Payments - Seprianti, Viola Ditya; Lubis, Irsad (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
Along with the rapid development of technology, the transformation of the payment system is also growing, especially in terms of non-cash payment systems. Considering that this payment system is one of the important components in the world economy and is also a work program of Bank Indonesia in order to improve the non-cash payment system to achieve better economic growth. This study aims to determine the level of understanding and benefits of non-cash payments on the use of non-cash payments in Binjai City. This study uses primary data obtained by distributing questionnaires and interviews. This study is a descriptive statistical study with a sample of 100 respondents in Binjai City. The results of the study Understanding of non-cash payments from respondents in the study have an effect on the use of non-cash payments such as electronic money or APMK in Binjai City. The benefits of non-cash payments from respondents in the study have an effect on the use of non-cash payments such as electronic money or APMK in Binjai City.